A study on the method for the capacity determination of water supply system in industrial complex - Song, Youngsun (KDI School, 2020)
In the past, many planners in the field of water use water consumption per land area although the circumstance of the industry is changing as time went on. The reason is that the method is simple to apply. Using 4.5 thousand data, this study examines which factors (land area, the number of employees, amount of product) are most closely related to the water consumption in industrial complexes. At first, whether the land area is statistically significant with water consumption. And then, the statistical significance is analyzed between the land area, the amount of production, the number of employees, and the water consumption. If the analytical values by the two methods are not statistically appropriate to use, the present middleclassification code of manufacture is reviewed by sub-classification or by a small group with sub-classification. This study is shown that water consumption in each manufacturer was not absolutely dependent on the land area due to the different nature of water consumption in each industry. For each code of manufacturing, a single variable (A(land area), E(number of employees), P(amount of product)) or many variables affects water consumption. Therefore, the sole application of land area unit when forecasting future industrial water use may not only lead to errors in the reliability of the forecasts but also affect the sizing of water supply facilities or sewage treatment facilities.
Thesis(Master) --KDI School:Master of Public Mangement,2020.